Development of Coaching Model for Enhancing KKMUNI Teachers’ Instruction in the 21st Century Skills - Maenyat, Suthasini (Journal of Teacher Professional Learning Community (JTPLC) (Online), 2021)
The development of coaching model for enhancing KKMUNI teachers’ instruction in the 21st century skills consists of five goals of the study. These included 1) studying the status quo and need of coaching model for developing instruction in the 21st century, 2) developing coaching model for developing instruction in the 21st century, 3) trailing of coaching model for developing instruction in the 21st century, 4) evaluation of implementing coaching model for developing instruction in the 21st century, and 5) contribution of coaching model for developing instruction in the 21st century. The findings revealed that coaching model for enhancing KKMUNI teachers’ instruction in the 21st century skills passed the effective criteria of 80/80 (82.14/89.07). It indicated that the coaching model held higher effective result than the determined criteria. It found that teachers held significantly (0.05) higher skills of instruction in the 21st century. Teachers’ satisfaction on the coaching model for instruction in the 21st century was categorized into the very good level. And, eighty percentages of students got higher score of 4 skills (analytical thinking, creative thinking, conceptual thinking, and learning skills in 21st century) than 80 percentages. And, students’ satisfaction on the KKMUNI instruction in the 21st century was categorized into the very good level.